The Effect of Navier Slip and Skin Friction on Nanofluid Flow in a Porous Pipe - Muyungi, W. N.; Mkwizu, M. H.; Masanja, V. G. (Engineering, Technology & Applied Science Research, 2022)
The flow of nanofluids through a porous medium is considered the optimum method for convective heat transfer. In this study, nanofluid flow in a porous pipe with Navier slip is investigated. Two water-based nanofluids, Copper (Cu) and alumina (Al2O3), were considered. The governing equation is presented and non-dimensionalization has been done for momentum and energy equations, initial and boundary conditions, skin friction, and Nusselt number. The governing system was simplified to ordinary differential equations, which were numerically solved and a mathematical model of nanofluid flow was formulated. The results, with regard to variations in various parameters such as temperature, velocity, skin friction, and Nusselt number, are presented graphically and discussed. It was found that the velocity during the flow decreases with the increase of the Navier slip.